Writing the research paper : multicultural perspectives for writing in English as a second language - McCarthy, Philip M.; Ahmed, Khawlah (London, England : Zed Books, 2021)
"Covering both theoretical and practical approaches, Writing the Research Paper guides students studying in English as a second or additional language through the skills necessary for success in university-level writing and research. The book begins with theoretical considerations, such as research, argumentation and critical thinking. It then offers a broad range of practical assistance covering all aspects of the writing process, including topic selection, argument, counter-argument, paragraph structure and cohesion. The book is accompanied by a companion website, writingtheresearchpaper.com. The website hosts many features, including chapter summaries, exercises, quizzes, PowerPoints, additional learning material, and technology assistance. The website also hosts numerous authentic examples of student papers at each of the critical stages of the writing process."--
Glossary -- Introduction -- 1. Critical Thinking -- 2. The Research Paper -- 3. Themes and Topics -- 4. The Thesis -- 5. Focused Research -- 6. Paraphrasing, Summarizing, Quoting, and Plagiarizing -- 7. Arguments and Evidence -- 8. Plans and Proposals -- 9. The Drafting Process -- 10. The Writer's Introduction -- 11. The Body -- 12. The Paragraph -- 13. Cohesion -- 14. The Conclusion -- 15. The Reader's Introduction -- Index
Includes index.
Also published in print.
Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Mode of access: World Wide Web.
Keywords: Technical writing -- Handbooks, manuals, etc; Writing -- Handbooks, manuals, etc; ELT: English for academic purposes; Electronic books